(untitled) (Annals of Medical Research, 2021)
Aim: Hypoglycemia is associated with excessive cardiovascular mortality because of the pro-inflammatory and pro-atherothrombotic pathway stimulation. Hypoglycemia is known to affect the development of sub-clinic atherosclerosis. This study aims to determine the development of sub-clinic atherosclerosis in patients with postprandial reactive hypoglycemia by investigating thickness of carotid intima media and epicardial fat, and high-sensitivity C-reactive protein values and their relationships with each other.Material and Methods: 51 patients in total were included in the project, including 28 patients (37.50±10.82 years) who had hypoglycemia symptoms and who had hypoglycemia during prolonged oral glucose tolerance test and 23 healthy adult volunteers (35.01±10.92 years) as a control group. Subjects underwent echocardiographic examination including EFT and IMT measurement using transthoracic echocardiography.Results: Postprandial Reactive Hypoglycemia group were marked with higher high-sensitivity C-reactive protein levels (1.67±0.67 vs. 1.20±0.52; p= 0.007), carotid intima media thickness (0.65±0.10 vs. 0.50±0.10; p0.001) and epicardial fat thickness (0.57±0.07 vs. 0.48±0.08; p= 0.001) values as compared to the control group.Conclusion: Patients with postprandial reactive hypoglycemia had impaired epicardial fat thickness and increased thickness of carotid intima media, and carotid intima media thickness linked with significantly with high-sensitivity C-reactive protein. These observations support the importance of chronic inflammation mechanism for the development of sub-clinic atherosclerotic disease in postprandial reactive hypoglycemia.